The Effect of Skin-To-Skin Contact during Heel Lance on the Physiological Parameters, Pain and Stress Level of the Term Newborn and Maternal Anxiety Level - Özge Kinaci; Sevda Arslan (Mediterranean Nursing and Midwifery, 2021)

(untitled)
Objective:The study was conducted at Sakarya University Hospital Obstetrics Clinic, in Sakarya Province, in Turkey, from January 2019 to February 2019, as a simple randomized (1: 1), experimental, and prospective study. It was aimed to evaluate effect of skin-to-skin contact (SSC) on physiological parameters, pain-stress level of newborn and anxiety level of mother during this stage.Method:In the study, 34 of 68 healthy term newborns were included control group, 34 of them were intervention group. Control group, no other intervention was done except routine applications to evaluate anxiety level of mothers. Intervention group, SSC with mother was ensured while drawing blood from heel and pain-stress level of newborn and its effect on level of anxiety of mother were studied.Results:When the results of ALPS-NEO Pain Scale were compared between groups, It was found that effect of SSC during heel lance on pain-stress level of newborns in intervention group was significantly lower than control group.Conclusion:As a result, SSC application can be used as a supportive method during heel lance, which is a painful procedure. However, there was no statistically significant result on anxiety of mothers.